Uso de Azospirillum brasilense e de Pseudomonas fluorescens no capim mavuno - Lima, Gabriel Pereira (2024)
Urochloa grass has been used for many years to raise rumunant animals, being the main bulky for these animals. However, most pastures have some degree of degradation and one of the causes is the lack of nutrient replacement. As the cost of fertilization, especially nitrogen, is high, the use of microorganisms to reduce these doses of chemical fertilizers can be one of the solutions to reduce production costs. The objective is to evaluate the productivity of Mavuno grass inoculated with plant growth-promoting bacteria, in order to reduce the cost of nitrogen fertilization. The experiment is already implemented at the Fazenda Escola of the State University of Goiás (UEG), West Campus, in the rural area of São Luís de Montes Belos. The experimental design was in randomized blocks, with 8 treatments and four repetitions. Treatments consist of: T1: control; T2: Azospirillum brasiliensis without N; T3: Pseudomonas fluorescens without N; T4: A. brasiliensis + P. fluorescens without N; T5: A. brasiliensis with 50 kg ha-1 of N; T6: P. fluorescens with 50 kg ha-1 of N; T7: A. brasiliensis + P. fluorescens with 50 kg ha-1 of N; T8: 100 kg ha-1 of N. It was conducted for a year and the treatments will be reapplied. The rate of green cover by grass, relative chlorophyll index, concentration of nutrients in the aerial part of the forage, accumulation of dry grass mass and amount of nutrients extracted by grass were evaluated. The inoculation of Mavuno grass, plus N, promoted the production of MS equal and even higher than the grass that was fertilized with the highest dose of N. The accumulated mean values (kg ha-1) in descending order in the first cycle were 182.7 N > 171.0 K > 36.5 Mg > 31.0 Ca > 11.2 S > 10.4 P and in the second cycle: 174.0 N > 154.8 K > 39.5 Mg > 37.0 Ca > 12.5 P > 11.2 S.